Health-Related Disinformation: Should We Focus More on Reducing the Mindware Gap or Corrupted Mindware? - Sunyik, Viktória; Čavojová, Vladimíra (Studia Psychologica, 2025)
The main aim of our study was to investigate whether COVID-19 conspiracy beliefs are driven by a lack of useful and potentially protective mindware or by contaminated mindware. On the quota sample of 501 adult Slovaks, we also investigated whether personally relevant content improves scientific reasoning by using two versions of scientific reasoning tasks – one with coronavirus scenarios and one neutral, but we found no effect. While probabilistic reasoning and scientific knowledge negatively predict belief inCOVID-19 conspiracy theories, anti-scientific attitudes significantly contribute to their higher acceptance. Thus, addressing anti-scientific attitudes and developing probabilistic reasoning and scientific knowledge may be crucial to attenuate health-related conspiracy beliefs.